2019
DOI: 10.1177/0733464819865685
|View full text |Cite
|
Sign up to set email alerts
|

Elder Abuse Characteristics Based on Calls to the National Center on Elder Abuse Resource Line

Abstract: Characterizing the types of elder abuse and identifying the characteristics of perpetrators are critically important. This study examined the types of elder abuse reported to the National Center on Elder Abuse (NCEA) resource line. Calls were coded with regard to whether abuse was reported, types of abuse alleged, whether multiple abuse subtypes occurred, and who perpetrated the alleged abuse. Of the 1,939 calls, 818 (42.2%) alleged abuse, with financial abuse being the most commonly reported (449 calls, 54.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 24 publications
16
38
0
2
Order By: Relevance
“…In our study, most of the older patients had been abused by family members: life partner (25.3%), children (33.7%), and other family members (18.1%). This finding is consistent with previous data, which reported that family members are the most commonly alleged perpetrators not only of financial abuse, but of all types of abuse; abuse by a family member was the most commonly reported relationship . In Romania there is a change in the traditional family and its values.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In our study, most of the older patients had been abused by family members: life partner (25.3%), children (33.7%), and other family members (18.1%). This finding is consistent with previous data, which reported that family members are the most commonly alleged perpetrators not only of financial abuse, but of all types of abuse; abuse by a family member was the most commonly reported relationship . In Romania there is a change in the traditional family and its values.…”
Section: Discussionsupporting
confidence: 92%
“…Data from previous studies states that abuse reflected the relative's problems and dependency on the victim rather than the older adult victim's characteristics or caregiver burden. Moreover, lack of social support and isolation may further place an isolated older person at risk of abuse by family members and other …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations